Phase II study with sorafenib plus radiotherapy for advanced HCC with portal and/or hepatic vein tumor thrombosis - Yirui Zhai; Liming Wang; Hong Zhao; Fan Wu; Lingxia Xin; Feng Ye; Wei Sun; Yan Song; Lijuan Niu; Huiying Zeng; Jingbo Wang; Yuan Tang; et al. (JHEP Reports)
Background & Aims: Portal and hepatic vein tumor thrombosis is associated with inferior outcomes in patients with hepatocellular carcinoma (HCC), and systemic treatment alone is often insufficient. This phase II trial evaluated the efficacy and safety of combining sorafenib with radiotherapy in advanced HCC with thrombosis. Methods: Registered at ClinicalTrials.gov (NCT03535259), this phase II single-arm prospective trial targeted patients with HCC with portal or hepatic vein tumor thrombosis, liver minus gross tumor volume >700 ml, and Eastern Cooperative Oncology Group Performance Status scores of 0 or 1. Participants underwent 40–66 Gy radiotherapy for the hepatic primary tumor and vein tumor thrombosis, with concurrent oral sorafenib (400 mg twice daily) until disease progression or unacceptable adverse events. The primary endpoint was median overall survival (mOS) and the secondary endpoints included overall response rate (ORR) per Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1 and Modified Response Evaluation Criteria in Solid Tumors (mRECIST), median progression-free survival (mPFS), time to tumor progression (TTP), tumor thrombosis control, and grade ≥3 adverse events. Results: Between May 2018 and January 2020, 86 patients were enrolled with a median radiotherapy dose of 54 Gy (40–65 Gy). At a median follow-up of 17.2 months, mOS, mPFS, and TTP stood at 16.5, 6.1, and 6.8 months, respectively. ORR reached 47.7% and 52.3% per RECIST and mRECIST, respectively. For the tumor thrombosis, 2-year control rates per mRECIST were 93.1%. No grade 5 adverse events were noted, whereas thrombocytopenia (22.1%) and leukopenia (14.0%) were the main grade 3 adverse events. Conclusions: Concurrent sorafenib and radiotherapy is an effective and well-tolerated treatment for patients with HCC with portal or hepatic vein tumor thrombosis. Impact and implications:: Treatment options for patients with hepatocellular carcinoma (HCC) and vascular tumor thrombus are limited. The efficacy and safety of concurrent sorafenib and radiation for HCC with portal or hepatic vein tumor thrombosis has not been elucidated. This phase II trial shows that concurrent sorafenib and radiotherapy is effective and well-tolerated in the treatment of advanced HCC with portal vein or hepatic vein tumor thrombosis. Clinical trials registration: This study is registered at ClinicalTrials.gov (NCT03535259).